Analysis of diesel degradative capacity by acidophilic microorganisms and its application as individual and consortium bioremediation system - Marián Alicia Hermoza Gutiérrez (2019)
The presence of hydrocarbons in soils and waters represents a serious problem of global environmental pollution, often caused by accidental spills of petroleum products such as diesel. Natural bioremediation is shown as an environmentally friendly alternative. The native communities of microorganisms present in a body affected by pollution, metabolicallycooperate with each other to survive; these have developed mechanisms of adaptation to adverse environments using the contaminating agent itself as a substrate. Currently, bioremediation systems require long times to obtain efficient degradation results; that is why, in the present investigation, microorganisms from a soil with the presence of diesel have been isolated from spills, for which the physicochemical characterization of contaminated soil was carried out. Next, two strains were isolated and molecularly identified, determining that the CR strain belongs to Kocurea Rosea and the CB strain to the Burkholderia pseudomallei, which grew inmedium enriched with glucose and diesel as substrates. The hydrocarbon degradation indicator parameters were evaluated: microbial concentration, hydrocarbon concentration, glucose concentration and pH variation in reactors provided with enriched liquid mineral medium whoseinitial pH was 5. The isolated strains achieved degradation percentages of 51.27% (Kocurea Rosea) and 32.84% (Burkholderia pseudomallei) of diesel, while the mixed native consortium degraded 48.78% of the diesel present in the medium during 13 days of residence time.